Financial Digitalization: Training in Recording MSME Financial Reports with the Help ofthe BukuWarung Application - Putri Aprilia (Jurnal Pengabdian Masyarakat, 2024)
Traditional markets serve a backbone for local economies in many countries, including Indonesia. Thesemarkets of er a lot of unique products and serve as central trading hubs for Micro, Small, and MediumEnterprises (MSMEs). In the digital era, free and user-friendly financial management applications haveemerged. However, MSMEs still face challenges in financial reporting due to time constraints and limitedunderstanding of its importance, and they often prefer manual record keeping. To address this, the authorsintroduced BukuWarung, a digital financial application, as a practical solution for more ef icientfinancial record-keeping. This project engagement project targeted clothing MSMEs in Yogyakarta’sCondongcatur and Beringharjo traditional markets. These markets are central to the local economy butlack awareness of financial reporting’s significance and technology adoption. The method used issocialization also training and mentoring that consists of four stages: observation, socialization, trainingand mentoring, and evaluation. The results demonstrated that the MSMEs understood financialimportance and ef ectively used BukuWarung for financial record-keeping. In conclusion, the projectsuccessfully introduced BukuWarung to improve financial awareness and capabilities among MSMEs inYogyakarta’s traditional markets.